2009
DOI: 10.1111/j.1365-2133.2008.08880.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of blood coagulation in bullous pemphigoid: role of eosinophils, and local and systemic implications

Abstract: The coagulation cascade is activated in BP and correlates with the severity of the disease and with eosinophilia, indicating that eosinophils play a role in coagulation activation via TF. The hypercoagulability may contribute to inflammation, tissue damage, blister formation and possibly thrombotic risk in BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(116 citation statements)
references
References 24 publications
11
100
1
4
Order By: Relevance
“…In fact Fujii and co-workers (48) found that the coagulation biomarkers that we routinely measure in patients with CU reflect an activation of the coagulation cascade that in CU occurs extravascularly, which may explain the low prevalence of thrombosis in this disease. In contrast, the activation of coagulation in patients with other skin diseases such as BP is associated with an increased thrombotic risk (9,88). Chronic urticaria is frequently characterized by the presence of elevated levels of plasma markers of thrombin generation and fibrinolysis during severe exacerbations of the disease (37,38,47), which can be due to the expression of TF by activated eosinophils (22).…”
Section: Discussionmentioning
confidence: 99%
“…In fact Fujii and co-workers (48) found that the coagulation biomarkers that we routinely measure in patients with CU reflect an activation of the coagulation cascade that in CU occurs extravascularly, which may explain the low prevalence of thrombosis in this disease. In contrast, the activation of coagulation in patients with other skin diseases such as BP is associated with an increased thrombotic risk (9,88). Chronic urticaria is frequently characterized by the presence of elevated levels of plasma markers of thrombin generation and fibrinolysis during severe exacerbations of the disease (37,38,47), which can be due to the expression of TF by activated eosinophils (22).…”
Section: Discussionmentioning
confidence: 99%
“…Marzano ve ark. yaptıkları bir çalışmada koagülasyon kaskadının aktive olduğunu, hiperkoagülabilitenin inflamasyon, bül formasyonu ve tromboz oluşumuna neden olduğu ve bu durumun hastalık şiddeti ile ilişkili olabildiğini savunmuşlardır 32 . BP'ye eşlik edebilen hastalıklar yaş ile de sıklığında artış olan hastalıklardır, bu nedenle birliktelik rastlantısal olabilir.…”
Section: Türk Dermunclassified
“…These changes were reversible by corticosteroid treatment. [31,32] Treatment options are mainly oral and/or topical superpotent corticosteroids frequently combined with immunomodulants such as dapsone and tetracyclines or immunosuppressant agents like azathioprine and methotrexate. [33,34] Recent reports about the successful treatment of individual BP patients with the anti-IgE antibody omalizumab [35][36][37][38][39][40] suggest a pathogenic relevance of IgE autoantibodies.…”
Section: Introductionmentioning
confidence: 99%